That continuous thing artists and the ceramics studio, 1920 - today - Matson, Sara; Thorne, Sam ca. 20./21.Jh (Tate Gallery Publishing, 2016)
From the rise of studio pottery in the 1910s to a number of new commissions by a young generation of UK-based artists, That Continuous Thing traces the changing shape of the ceramics studio over the last century, from the radical to the apparently traditional. Opening with exchange between Japan and the UK in 1910s and 1920s through the emergence of studio potters such as Bernard Leach, Shoji Hamada and Dora Billington, the book leads on to the Californian clay revolution of the 1950s and 1960s, with sculptures by the pioneering artist Voulkos. The book also includes works by contemporary artists made over the last three years at Angells London-based Troy Town Art Pottery, which has been described as a radical and psychedelic workshop for artists. 0Exhibition: Tate St. Ives, St. Ives, UK (21.05-02.10.2016)